Multi-storey precast concrete framed structures - Elliott, Kim S. (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
Precast reinforced and prestressed concrete frames provide a high strength, stable, durable and robust solution for any multi-storey structure, and are widely regarded as a high quality, economic and architecturally versatile technology for the construction of multi-storey buildings. The resulting buildings satisfy a wide range of commercial and industrial needs. Precast concrete buildings behave in a different way to those where the concrete is cast in-situ, with the components subject to different forces and movements. These factors are explored in detail in the second edition of Multi-Stor.
Precast concepts, history and design philosophy -- Procurement and documentation -- Architectural and framing considerations -- Design of skeletal structures -- Design of precast floors used in precast frames -- Composite construction -- Design of connections and joints -- Designing for horizontal load -- Structural integrity and the design for accidental loading -- Site practice and temporary stability.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed April 4, 2014).
Keywords: Precast concrete construction; Tall buildings -- Design and construction; TECHNOLOGY & ENGINEERING -- Construction -- General; Precast concrete construction; Tall buildings -- Design and construction; Precast concrete construction; Tall buildings -- Design and construction; Electronic books; Electronic books